2017
DOI: 10.21106/ijma.196
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in HIV-Infected Women: Experience from a Tertiary Care Center in India

Abstract: Background and Objectives:There is conflicting data on the effect of HIV infection as well as antiretroviral therapy (ART) on pregnancy outcome. The objectives of this study were to compare pregnancy outcomes in women with and without HIV infection, and to evaluate the effect of HAART on pregnancy in HIV-infected women.Methods:This is a prospective case record analysis of 212 HIV-infected women delivering between 2002 and 2015, in a tertiary health care center in India. The pregnancy outcome in HIV-infected wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 18 publications
5
28
1
2
Order By: Relevance
“…In studies done by Shiradkar et al,and Dadhwal et al,76.95% and 80% partners tested positive respectively. 6,15 Mohite et al reported a partner testing rate of 54.9%, with an increasing trend of acceptance over the years, as stated in our study. 9 In our study 50.88% of the antenatal seropositive mothers were primigravidas, with majority being housewives from low income classes, with a very poor educational background.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In studies done by Shiradkar et al,and Dadhwal et al,76.95% and 80% partners tested positive respectively. 6,15 Mohite et al reported a partner testing rate of 54.9%, with an increasing trend of acceptance over the years, as stated in our study. 9 In our study 50.88% of the antenatal seropositive mothers were primigravidas, with majority being housewives from low income classes, with a very poor educational background.…”
Section: Resultssupporting
confidence: 87%
“…et al, there were 11.53% abortions, and 76.15% delivered vaginally and 12.30% by Radhika et al, reported an abortion rate of 10.3%, and caesarean section rate of 43.6% 8. We had a NICU admission rate of 19.46%, whereas Dadhwal et al, had a NICU admission rate of 8.5% 15. …”
mentioning
confidence: 66%
“…For the pregnant woman, recognizing herself as infected by the virus implies the need to redefine the value of her own life and that of the fetus being generated, as well as the meanings of interpersonal relationships and even their own death 14 . Thus, having knowledge of their positive serology during pregnancy, the woman suffers an intense psychological impact 15 .…”
mentioning
confidence: 99%
“…9 On the contrary, in study done by Dadhwal et al, the mean birth weight was lower in new born of HIV infected women. 10 Brocklehurst et al and Xiao PL reported that LBW and PTD were associated with maternal HIV infection. 11,12 Habib et al, has also shown an association between maternal HIV status and preterm labour.…”
Section: Discussionmentioning
confidence: 99%